SPECTRA: An Integrated Knowledge Base for Comparing Tissue and Tumor-Specific PPI Networks in Human - Micale, Giovanni; Ferro, Alfredo; Pulvirenti, Alfredo; Giugno, Rosalba (Frontiers in Bioengineering and Biotechnology, 2015)
Protein-protein interaction (PPI) networks available in public repositories usually represent relationships between proteins within the cell. They ignore the specific set of tissues or tumors where the interactions take place. Indeed, genes can form tissue-selective complexes, while they remain inactive in other tissues. For these reasons, a great attention has been recently paid to tissue-specific PPI networks, in which nodes are proteins of the global PPI network that are preferentially expressed in specific tissues. In this paper we present SPECTRA, a knowledge base to build and compare tissue or tumor specific PPI networks. SPECTRA integrates gene expression and protein interaction data from the most authoritative online repositories. We also provide tools for visualizing and comparing such networks, in order to identify the expression and interaction changes of proteins across tissues, or between the normal and pathological states in the same tissue. SPECTRA is available as a web server at http://ferrolab.dmi.unict.it/spectra/spectra.php